Front Cover: Naphthalenediimides with Cyclic Oligochalcogenides in Their Core (Chem. Eur. J. 62/2020). Issue 62 (1st October 2020) - Shybeka, Inga; Aster, Alexander; Cheng, Yangyang; Sakai, Naomi; Frontera, Antonio; Vauthey, Eric; Matile, Stefan
Abstract : The colorful chemistry in the core of naphthalenediimides, aka NDIs, is represented by the Warholesque cover image, here with green, (infra)red‐fluorescent cyclic trisulfides, members of cell‐penetrating cyclic oligochalcogenides, and their photoinduced contraction into yellow cyclic disulfides. Absorption shifts by more than 170 nm because the through‐space distance between O and S increases by as little as 0.4 Å. More information can be found in the Communication by E. Vauthey, S. Matile, et al. on page 14059 .